The transition of a traditional newspaper to the internet age: a historical account of Le Monde’s case - Mesquita, Rafael (Observatorio (OBS*), 2017)
This essay analyzes how traditional media has dealt with the arrival of the internet age, examining its reactions and efforts to adapt to this new environment. For such, we will explore the case of the French daily Le Monde, which carries a long and renowned tradition in print and, therefore, faced numerous challenges to adjust itself to the digital domain, having to overcome barriers in its organization culture, newsroom workflow and business models until a suitable strategy was found to ensure its competitiveness. The investigation is supported by historical bibliographic review and original interviews with personnel from the media group.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTU4NDcvb2Jzb2JzMTEwMjAxNzEwMzY